ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI BENTUK ALJABAR - Robiatul Maghfiroh; Siti Khabibah; Gunanto Amintoko (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
This research aims to describe the problem solving skills of students in grade VIIILIPS BI and the factors that cause or affect students have low, moderate, and high problemsolving abilities. This research is a qualitative descriptive study. The subjects in this studywere 19 students of Grade VIII LIPS BI SMP Nurul Jadid Paiton Probolinggo. Theinstruments in this study are test and interview instruments. The data collection techniques inthis study are test and interview methods. While, the data analysis techniques in this study aredata reduction, data presentation and drawing conclusions. The results showed that therewere 6 students with high problem solving skills, 12 students who had moderate problemsolving skills, and there was only one student with low problem solving skills. The polya stagethat is difficult for students to do in the problem solving skills test is the second polya step,which is at the stage of making a problem solving plan. While the contributing factor to theproblem-solving skills of grade VIII students is a lack of appreciation for math lessons,students lack interest in math lessons and students dislike mathematics